Interaction of Shear Wall with Elastic Foundation Under the Excitation of SH Waves - Gamer, U.; Pao, Y.-H. (Engineering Transactions, 1977)
The study of the interaction between soil and structure was started by J.E. Luco (1969) who treated an infinite shear wall on a rigid foundation of semi-circular cross section under the excitation of a plane harmonic SH wave. M.D. Trifunac (1972) found that the motion of this structure is independent of the angle of incidence. In this paper, an elastic foundation is considered. Furthermore, a rigid mass on top of the shear wall is added. However, the boundary conditions at the inte-face between foundation and shear wall are satisfied only in average over the width of the latter. The numerical results are compared to those of the rigid foundation case. There are considerable differences.